2017
DOI: 10.4236/jcdsa.2017.72014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Regional Climate and Aging on Seasonal Variations in Chinese Women’s Skin Characteristics

Abstract: OBJECTIVES: Skin characteristics change depending on the external environment such as UV, temperature and humidity. But the research how to affect the regional climate, age and seasonal variation on the skin conditions was not well studied. Therefore, we investigated the seasonal variation in the skin by comparing Beijing women and Guangzhou women by age groups. METHODS: 440 healthy Chinese women participated in this study. The skin hydration, sebum secretion, TEWL and skin pH were measured on the cheek front.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 17 publications
5
12
0
Order By: Relevance
“…1). The vast majority of the studies found decreased SC hydration in winter as we also confirmed 11‐32 . Only a few studies observed no or opposite trends in some specific cases 13,16‐18,33 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…1). The vast majority of the studies found decreased SC hydration in winter as we also confirmed 11‐32 . Only a few studies observed no or opposite trends in some specific cases 13,16‐18,33 …”
Section: Discussionsupporting
confidence: 82%
“…Then, a reduced number of total ceramides, fatty acids, cholesterol, 62‐65 increased ratio of ceramides with shorter chains, 17 and containing unsaturated fatty acids 63 were found in winter skin in comparison with summer possibly contributing to a decreased water resistance of SC in winter 66,67 . These changes can be partly explained by often observed higher pH in winter 16,19,22,25,28,31,68 caused by the lack of the skin sebum and acidic NMF molecules from the sweat and leading to a decreased activity of lipid processing enzymes such as β‐glucocerebrosidase and acidic sphingomyelinase 69 . Higher pH also activates serine proteases leading to protease‐activated receptor 2 (PAR2) activation which then inhibits secretion of lamellar bodies necessary for the proper skin barrier formation 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The hydration data indicate that seasons had a strong effect on the skin moisture content. These observations are in line with studies by Lie, showing that skin hydration is decreased in a dry season than a hot and wet summer [22]. Any effect of Pycnogenol ® intake on the skin moisture content of the skin was therefore likely submerged by the seasonal effects.…”
Section: Discussionsupporting
confidence: 91%
“…This reverse relationship under high temperature and high humidity conditions in summer in Beijing may explain why the basal hydration but not the basal TEWL at week 13 significantly increased (Fig. 2c, d) [18, 22]. The change of TEWL after 19 and 25 weeks of treatment was significantly different between both groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…affect acquired skin features [21] [22] [23]. Scalp and hair might be influenced in a similar way to facial skin.…”
Section: Discussionmentioning
confidence: 99%